Effect of catalytic systems on the hydrogenation of phenanthrene - Aitbekova, D.E.; Su, Xintai; Ma, Fengyung; Tusipkhan, A.; Baikenov, M.I. (KSU publ., 2019)
This paper shows the effectiveness of the synthesized catalytic additives in the process of hydrogenation of phenanthrene in the presence of ethanol as a hydrogen donor. Ferrosphere, NiO/SiO2 covered the surface of ferrosphere and Fe2O3/SiO2 covered the surface of ferrosphere were used as catalytic additives. Ferrosphere was extracted from energy ashes of Karaganda thermal power plant. NiO/SiO2 and Fe2O3/SiO2 covered the ferrosphere were prepared by the method of «wet mixing». The phase composition, surface morphology, average size and distribution of particles of ferrospheres and nanocatalytic additives NiO/SiO2 and Fe2O3/SiO2 covered the ferrospheres were determined. The composition of the reaction products was determined by the method of chromato-mass spectrometry on the gas chromatograph of Agilent Technologies 7890A with mass spectrometric detector 5975C. Identification of the substances was carried out using the NIST 98 massspectral database. A synergistic effect of nanocatalytic additives NiO/SiO2 and Fe2O3/SiO2 covered the ferrospheres was established. The high degree of phenanthrene conversion is observed on the hydrogenation in the presence nickel and iron catalytic additives on the ferrosphere. According to the results of hydrogenation of phenanthrene efficiency range of the catalytic additives was built: NiO/SiO2 on the ferrosphere > > Fe2O3/SiO2 on the ferrosphere > NiO/SiO2 > Fe2O3/SiO2 > ferrosphere.
Keywords: polyaromatic hydrocarbons; phenanthrene; hydrogenation; catalytic systems; ferrosphere; sol-gel method; «wet mixing» method; coal